1995
DOI: 10.1017/s0960258500002786
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiology of germination in the aromatic plants thyme, savory and oregano (Labiatae)

Abstract: Ecophysiological aspects of seed germination were investigated in the widely distributed Mediterranean-endemic, aromatic plants thyme (Coridothymus capitatus), savory (Satureja thymbra) and oregano (Origanum vulgaresubsp.hirtum). Thyme seed germination is light indifferent, whereas oregano seeds have an absolute light requirement; their germination can be promoted even by green safelight or far-red light. In savory, a portion of the seeds germinates in the dark and germination can be either increased or decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0
7

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 18 publications
8
51
0
7
Order By: Relevance
“…Regarding the effects of temperature, the highest germination percentage was obtained at 15 ºC. These results are in agreement with those of Thanos et al (1992Thanos et al ( , 1995, who found that the optimal germination temperature for most Mediterranean shrub species ranges between 15 ºC and 20 ºC, and with previous data on P. angustifolia seeds collected at a different geographical location (Mira et al, 2015b).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the effects of temperature, the highest germination percentage was obtained at 15 ºC. These results are in agreement with those of Thanos et al (1992Thanos et al ( , 1995, who found that the optimal germination temperature for most Mediterranean shrub species ranges between 15 ºC and 20 ºC, and with previous data on P. angustifolia seeds collected at a different geographical location (Mira et al, 2015b).…”
Section: Discussionsupporting
confidence: 92%
“…Also, temperature regime for P. latifolia was very restrictive, since seeds did not germinate at either 25 ºC or 25/15 ºC. These results are in agreement with optimal germination temperature for most Mediterranean shrub species ranging between 15 ºC and 20 ºC (Thanos et al 1992(Thanos et al , 1995. Alternating temperatures (20/7 ºC and 25/15 ºC) resulted in low germination percentages, although previous works stated that Phillyrea seeds germinated a 90% after 60 days at 20/7 ºC (Herranz et al 2006), or a 90%…”
Section: Discussionsupporting
confidence: 72%
“…After two months they started to germinate. Other studies on germination temperatures for most Mediterranean shrub species suggest 15-20 °C as optimal temperature (Thanos et al 1992(Thanos et al , 1995. Concerning stratification, the cold stratification at 2-4 °C for all the combinations of chemical pre-treatments resulted in zero germination, while warm stratification at 15°C significantly increased the germination.…”
Section: Discussionmentioning
confidence: 74%